Developing the Higher Education Curriculum Research-Based Education in Practice (University College London, 2017)
A complementary volume to Dilly Fung's A Connected Curriculum for Higher Education (2017), this book explores 'research-based education' as applied in practice within the higher education sector. A collection of 15 chapters followed by illustrative vignettes, it showcases approaches to engaging students actively with research and enquiry across disciplines. It begins with one institution's creative approach to research-based education - UCL's Connected Curriculum, a conceptual framework for integrating research-based education into all taught programmes of study - and branches out to show how aspects of the framework can apply to practice across a variety of institutions in a range of national settings. The 15 chapters are provided by a diverse range of authors who all explore research-based education in their own way. Some chapters are firmly based in a subject-discipline - including art history, biochemistry, education, engineering, fashion and design, healthcare, and veterinary sciences - while others reach across geopolitical regions, such as Australia, Canada, China, England, Scotland and South Africa. The final chapter offers 12 short vignettes of practice to highlight how engaging students with research and enquiry can enrich their learning experiences, preparing them not only for more advanced academic learning, but also for professional roles in complex, rapidly changing social contexts.